2016
DOI: 10.1016/j.applanim.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tank background on the welfare of the African clawed frog, Xenopus laevis (Daudin)

Abstract: Impact of tank background on the welfare of the African clawed frog, Xenopus laevis (Daudin)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…It also allows for sampling the same individual multiple times and over long periods of time, even of small animals that would otherwise have to be sacrificed (Scott & Ellis, 2007). Many studies have provided evidence that water-borne corticosterone provides physiologically relevant estimates that are biologically meaningful (Baugh et al, 2018;Charbonnier et al, 2018;Davis et al, 2019;Gabor et al, 2013Gabor et al, , 2015Gabor et al, , 2016Gabor et al, , 2018Holmes et al, 2016). Because water-borne hormone sampling is still a new method, additional research is necessary to determine the ideal containment time (1 hr, 2 hr, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It also allows for sampling the same individual multiple times and over long periods of time, even of small animals that would otherwise have to be sacrificed (Scott & Ellis, 2007). Many studies have provided evidence that water-borne corticosterone provides physiologically relevant estimates that are biologically meaningful (Baugh et al, 2018;Charbonnier et al, 2018;Davis et al, 2019;Gabor et al, 2013Gabor et al, , 2015Gabor et al, , 2016Gabor et al, , 2018Holmes et al, 2016). Because water-borne hormone sampling is still a new method, additional research is necessary to determine the ideal containment time (1 hr, 2 hr, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…In common midwife toads, Bd infection and higher corticosterone levels were associated with decreased ability of their righting reflex (Gabor et al, ). African clawed frogs ( Xenopus laevis ) in tanks with an unnatural background color (white) had higher levels of water‐borne corticosterone along with greater body mass loss (Holmes et al, ). The measurable responses in water‐borne corticosterone levels coupled with biological responses indicate an association between water‐borne corticosterone levels and the treatments that is biologically relevant.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Laura Scullion Hall and colleagues at the University of Stirling and AstraZeneca have recently shown that beagles housed in a purpose-built facility with modern home pen design and exposed to regular staff contact and training demonstrate more signs of positive welfare (for example, resting) and fewer negative signs (for example, vigilance and stereotypies) than do beagles housed in traditional housing 15 . Lottie Hosie, at the University of Chester, found that Xenopus laevis housed in tanks with dark (ecologically relevant) backgrounds showed fewer signs of stress (lower corticosterone release rates in females, a small proportion of atypical locomotor behaviors and snout abrasions in both sexes, and a smaller drop in body mass) than those kept in tanks with white backgrounds 16 . Often, this is the kind of information required by the animal facility senior management team to justify committing funds to improve housing standards.…”
Section: Research To Generate An Evidence Base For Improvements In Humentioning
confidence: 99%